Penerapan Inovasi Produk dan Manajemen Mutu dalam Meningkatkan Daya Saing Produk UMKM di Desa Aek Loba Afdeling 1 - Vira Aurel; Abu Yazid Raisal (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
One of the factors that influences the competitiveness of MSME products is their ability to innovate and manage product quality. Product innovation allows MSMEs to create added value and differentiate themselves from competitors, while good quality management ensures the consistency and quality of the products produced. This community service activity was carried out in order to increase the self-awareness of the community, especially the MSMEs in Aek Loba Afdeling 1 Village, Aek Kuasan District, Asahan Regency. The method used in this community service is face-to-face (om the spot training). Data collection used was observation, interviews and documentation. The result of this community service is increasing public understanding of the importance of product innovation and quality management in increasing the competitiveness of MSME products